A new dimension of foreign investment law in China – evolution and impacts of the national security review system. Issue 2 (5th December 2016) - Li, Yuwen; Bian, Cheng
ABSTRACT: This article discusses the evolutional trajectory of China's national security review system (NSRS) and its potential impacts on inward foreign investment. By analysing the law-making process as well as merger cases of major significance, this article explores the emergence of China's NSRS in 2003, followed by its decade long (2006–2015) legal construction. The formation process of the NSRS that has evolved from interim administrative regulations to national law complies with the pragmatic, incremental character of the law-making in China in general. The key features of the NSRS provided in the 2015 draft Foreign Investment Law (FIL) is examined in detail to demonstrate the legislative headway as well as room for further refinement. In response to the ongoing concerns on the potential impacts of the NSRS on future foreign investment in China, this article attempts to argue that China's newly established NSRS, set forth in Chapter 4 of the draft FIL, is an anticipated and rational outcome, though further modification of the relevant provisions in the final text of the FIL could be expected. While the NSRS might cause rejection or delay of approval to some foreign investment projects, the clarified and delineated NSRS offers greater legal certainty and predictability. In view of China's continuous and adamant policies of attracting foreign direct investment (FDI), the NSRS is unlikely to have a significant impact on most foreign investment projects in the future.